Dual Hysteresis Model of MR Dampers - Janusz Gołdasz; Janusz Gołdasz; Bogdan Sapiński; Łukasz Jastrzębski; Michal Kubik (Frontiers in Materials, 2020)
This study concerns the modeling of the hysteretic behavior of magnetorheological (MR) dampers. In general, hysteresis is one of key factors influencing the output of such actuators. So far, more attention has been paid to studying the combined hysteretic behavior of MR actuators by observing the relationships between the output (force/torque) and the inputs (current, velocity, and position). However, these devices feature two distinct hysteretic mechanisms: mechanical/hydraulic and magnetic. The mechanical hysteresis is of different nature than the magnetic hysteresis due to the properties of ferromagnetic materials forming the actuator's electromagnet circuit, and these should be split in the modeling process. In the present study, we separate the magnetic hysteresis from the mechanical/hydraulic one by investigating the magnetic flux vs. exciting current relationship of a commercial flow-mode MR damper subjected to sinusoidal current loading and independently of the mechanical excitations. The resulting behavior of the electromagnetic circuit is then examined using the non-linear inductor approach with hysteresis. Total hysteresis is then modeled using a non-linear inductor model in combination with a phenomenological parametric Maxwell type model of the damper.